The Role of Asian International Arbitration Centre (AIAC) as a Regional Hub for Oil and Gas Sector - M. Zulhafiz, Wan (International Journal of Engineering and Technology, 2018)
Hydrocarbons projects involve multiple parties, including sovereign states and corporations, to operate expensive, complex and high-risk activities. Alternative dispute resolution (ADR) is often preferred more by the parties than litigation to ensure the smooth running of the projects. ADR refers to all mechanisms of dispute settlement other than litigation such as negotiation, mediation, adjudication, and arbitration. The Asian International Arbitration Centre (AIAC) or formerly known as the Kuala Lumpur Regional Centre for Arbitration (KLRCA) is the main institution that administers and resolves all commercial arbitration disputes in Malaysia. This research argues that, due to the technicalities and complexity of operations in the oil and gas sector, there is a need to set up a special arbitration centre for oil and gas under the AIAC to handle and resolve the industrial disputes. Furthermore, by establishing the centre, it can help to promote the AIAC as the choice of arbitration hub, especially within the Organization of the Petroleum Exporting Countries (OPEC). In doing so, it is necessary to pass a special legal framework to enable the establishment of the centre. It may function as a roadmap by the key players of the oil and gas sector to recourse in resolving disputes. The methodology employed by this research is carried out in a prescriptive, comparative and analytic manner.Â Â